Antioxidant properties of some novel derivatives thiazolo[4,5-b] pyridine - Taras Chaban; Volodymyr Ogurtsov; Anatoliy Mahlovanyy; Natalia Sukhodolska; Ihor Chaban; Stefan Harkov; Vasyl Matiychuk (Pensoft Publishers, 2019)
The synthesis and determination of the antioxidant activity of some novel (5,7-dimethyl-2-oxo-thiazolo[4,5-b]pyridine-3-yl)-acetic acid hydrazide derivatives are described in this article. The transformation of the base heterocycle was carried out via the reactions of acylation, [2+3]cyclocondensation, Knoevenagel condencation and alkylation for the purpose to obtain substances with a satisfactory pharmacological profile. Antioxidant activity of the synthesized compounds was evaluated in vitro by means of the scavenging metod effect on 2,2 diphenyl-1-picrylhydrazyl (DPPH) radicals.